PENDIDIKAN KESEHATAN INHALASI SEDERHANA TERHADAP TINGKAT PENGETAHUAN KELUARGA DENGAN ASMA DI WILAYAH KERJA PUSKESMAS SELOGIRI - Ratnasari, Nita Yunianti; Yuliana, Vena (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
Asthma is a chronic inflammation of the airways. Chronic airways that have chronic inflammation are hyperresponsive so that when stimulated by certain risk factors, the airway becomes blocked and the air flow is obstructed due to bronchial constriction, mucous congestion, and increased inflammation. Lack of patient and family knowledge can increase the risk of asthma complications. To improve the prevention of complications, health education in simple inhalation therapy is given. The purpose of this study was to determine the effect of health education on simple inhalation therapy on the level of knowledge of families of asthmatics. The method used in this research is descriptive case study which is one type of strategy in qualitative research with a case study research approach (case study). The population in this study was all of the Tandan Village, Kepatihan Village, Selogiri Subdistrict, which are included in the work area of the Selogiri Community Health Center who suffer from asthma. Sample of 3 family respondents with asthma. The action taken was simple inhalation health education. This health education is carried out 1 day for 1 hour. All three family respondents experienced an increase in knowledge as evidenced by the ability to answer the questionnaire before and after being given health education, from the inadequate category (33% - 53%) to the moderately good category (73% -100%). From the case study it was found that the level of respondents' knowledge increased as evidenced by the ability to answer the questionnaire before and after being given health education, from the category of inadequate (33% -53%) to the category of fairly good (73% - 100%). The increase in the level of knowledge is influenced by the level of education, socioeconomic, age, and experience of obtaining previous health education